The Meaning and Content of the Steam Educational Approach in the Development of Students' Creative Thinking - Yuldoshev Jahangir Tilakmurodovich (Researchparks Publishing, 2022)
The article describes the content of STEAM tasks, their role in improving the effectiveness of training, methods for completing tasks.